Phytoremediation of heavy metal (copper and lead) using impatiens balsamina associated with pseudomonas sp. / Siti Nabila Mohamad Saleeh - Mohamad Saleeh, Siti Nabila (Faculty of Applied Sciences, 2014)
Phytoremediation is a process to treat heavy metal contaminated soil by plant. Some of phytoremediation process used bacteria to help the removal of heavy metal from contaminated soil. The objective of this study is to determine the tolerance concentration (MIC value) of Pseudomonas sp. towards heavy metal and to measure phytoremediation process by Pseudomonas sp. bacteria with Impatiens balsamina plant. This studied covered from enrichment of Pseudomonas sp. in nutrient agar with the present of copper (Cu) and Lead (Pb). Analysis were carried out using three types of soil treatment samples includes control soil, heavy metal soil and heavy metal with 10% inoculum Pseudomonas sp. soil. All samples were analysed by using Atomic Absorption Spectroscopy (AAS) after 14 days phytoremediation process. From Minimum Inhibitory Concentration (MIC) method, it was found that Pseudomonas sp. can tolerate and survive with 90 ppm of copper (Cu) and 300 ppm of lead (Pb). Based on the results, the highest removal of heavy metal were done by using Impatiens balsamina only which 29.41 % were for copper (Cu) and 49.24 % for lead (Pb). But, in the present of bacteria, Pseudomonas sp. was unable to improve removal of heavy metal (Cu: 14.53% and Pb: 33.50%). Therefore, the plant itself has the potential to remove heavy metal from contaminated soil.